Estimation of a Mechanization Index and Its Impact on Energy and Economic Factors in Apple Orchard in Iran - Fadavi, Raheleh; Keyhani , Alireza; Mohtasebi, Seyyed Saied (Asian Journal of Agriculture and Rural Development, 2012)
This study was conducted in the 2008-9 production year in West Azerbaijan province (Uromia Township). The Energy Ratio, Energy Productivity, Economic Productivity and Mechanization Index were estimated for apple production. Data were collected using random sampling for 80 face-to-face respondents. Results showed that the highest share of energy consumption belongs to packaging (57%) followed by irrigation (16%). The highest share of expenses was found to be 34% and 30% for labour and packaging, respectively. Mechanization was considered at three levels including level 1 for spraying only, level 2 for spraying and plotting, and level 3 for spraying and fertilizing operations. The Energy Ratio was found to be less than one for all mechanization levels having the highest value in level 2 (0.58). The highest economic productivity was calculated as 1.9 for level 2. Results showed that increasing the Mechanization Index, will not necessarily increase energy ratio and economic productivity.